Collective work characteristics in business information system development - Gava, Vagner Luiz; Spinola, Mauro Mesquita; Gonçalves, Rodrigo Franco; Medina, José Cardenas; Tonini, Antonio Carlos (Revista Gestão da Produção Operações e Sistemas, 2014)
System information development methodologies have developed greatly in recent years. However, although most of them take into account user’s involvement and participation in several development process phases, none of them have explicitly considered the issue of cooperative work in the design of business information systems, or its use. A model using Ergonomics techniques, cognitive mental models and classical engineering is presented. This model is applied during the development of a corporate workflow system in a Brazilian technological research company. The application was done through action research Methodology. It has allowed us to demonstrate the need of discovering the most important and common points in the users’ activities and the construction of the collective image of the system. Finally, the model limitations are discussed as well as the the research design continuity. Keywords: Collective analysis at work; Ergonomics; Software Prototyping; Mental Models; Software Development.